Faceted Classification and Multi-Viewpoints Models: Differences and Complementarities - Mas, Sabine; Benel, Aurelien; Cahier, Jean-Pierre; Zacklad, Manuel (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Because of their similarities, faceted classification (in Information Science) and multi-viewpoints modelling (in Knowledge Engineering) are often mistaken. This paper presents both theoretical and practical differences. Then it describes their joint use and their complementarities for content management in a large organization. La modélisation multi-points de vue telle qu’utilisée en ingénierie des connaissances est parfois confondue avec la classification multi-facettes telle que comprise en bibliothéconomie et sciences de l’information. Cet article tente de les distinguer tant au niveau théorique que sur des exemples pratiques. Il décrit ensuite leur utilisation conjointe et leur complémentarité dans la gestion de contenu d’une grande entreprise.